The Influence of Financial Attitudes and Financial Knowledge on the Financial Management Behavior of Mobile Counter MSME Actors in Binawidya District, Pekanbaru City - Sintia, Lola; Ruzikna, Ruzikna (CV. Rayyan Dwi Bharata, 2024)
This research was conducted on mobile phone counter MSMEs in Binawidya District, Pekanbaru City regarding the influence of financial attitudes and financial knowledge on financial management behavior. This research involved 95 respondents from 124 populations who were calculated using the Slovin formula. The data collection method in this research was by distributing questionnaires to 95 respondents spread across five sub-districts in Binawidya District, Pekanbaru City, determining the number of samples for each sub-district using the proportional stratified random sampling technique, then the data was processed and tested using SPSS. So the results obtained are that partially financial attitudes have a positive and significant effect on financial management behavior, then partially financial knowledge has a positive and significant effect on financial management behavior and also simultaneously financial attitudes and financial knowledge have a positive and significant effect on the financial management behavior of MSME players. cellphone counter in Binawidya District, Pekanbaru City.